Operation of The Hybrid Energy Resources with Storage System Participation - Candra, Oriza; Huamán-Romaní, Yersi-Luis; Hammid, Ali Thaeer; Romero Parra, Rosario Mireya; Hamad, Hassan Salman; Rodas – Guizado, Efraín; Kadhim, Sokaina Issa; Zearah, Sajad Ali (International Journal of Integrated Engineering, 2023)
This paper focused on the optimal operation of the hybrid energy resources in the off-grid state considering energy storage participation. The hybrid energy resources consist of wind turbine (WT), photovoltaic (PV), diesel generator (DG), and energy storage system for supplying energy to DC and AC load demand with maximum reliability. The operation of the proposed energy system based on energy control and energy optimization is modeled. The energy optimization and energy control are implemented by heuristic and nonlinear quadratic programming approaches via optimal power flow on the resources side. The energy control is done based on the weight sum method in different operation states of the system. Also, the impact of the energy storage system on the hybrid energy resources is considered as backup resources. The energy control modeling is implemented via mathematical simulation and numerical analysis in the two operation states in the summer and winter seasons for verifying the proposed approaches. Finally, the results of the energy control show optimal states of the energy system in supplying demand with considering the energy storage system.